Diagnosis of watershed Yuqueza River in the community of San Lorenzo Albarradas, Oaxaca - Martínez de la Cruz Judith; Díaz Zorrilla Gustavo Omar; Lozano Trejo, Salvador; Pérez León María Isabel; Vásquez Valentín (Revista Mexicana de Ciencias Agrícolas, 2018)
The elaboration of diagnostic constitutes a set of actions oriented to gather the necessary information and available to achieve the best possible knowledge about the basin or watershed, its problems and its causes. The objective of this study was to assess the natural resources in the watershed Yuqueza River under watershed approach management in San Lorenzo Albarradas, Oaxaca during the period of August 2009 to July 2011. It was used the methodology from the Mexican Institute of Water Technology (IMTA) to recognize the importance of socio-economic activities that are developed in the watershed. It focuses on the rehabilitation of watersheds and the influence of anthropogenic activities on natural resources. The watershed Yuqueza River works as a water reservoir used for the population. The agricultural, forestry and livestock practices, thus as overgrazing, roads construction and trails have accelerated the degradation of the watershed. This has led to the decline in productivity in agroecosystems, decreased natural availability of water and soil loss, nutrients and organic matter. By its extension of 453 hectares is classified as nano watershed; from the elongation morphometric analysis was determined that its shape is elongated.